Prevalence, Awareness, Treatment, and Control of Hypertension among Saudi Adult Population: A National Survey - Abdalla A. Saeed; Nasser A. Al-Hamdan; Ahmed A. Bahnassy; Abdelshakour M. Abdalla; Mostafa A. F. Abbas; Lamiaa Z. Abuzaid (International Journal of Hypertension)
This cross-sectional study aimed at estimating prevalence, awareness, treatment, control, and predictors of hypertension among Saudi adult population. Multistage stratified sampling was used to select 4758 adult participants. Three blood pressure measurements using an automatic sphygmomanometer, sociodemographics, and antihypertensive modalities were obtained. The overall prevalence of hypertension was 25.5%. Only 44.7% of hypertensives were aware, 71.8% of them received pharmacotherapy, and only 37.0% were controlled. Awareness was significantly associated with gender, age, geographical location, occupation, and comorbidity. Applying drug treatment was significantly more among older patients, but control was significantly higher among younger patients and patients with higher level of physical activity. Significant predictors of hypertension included male gender, urbanization, low education, low physical activity, obesity, diabetes, and hypercholesterolemia. In conclusion prevalence is high, but awareness, treatment, and control levels are low indicating a need to develop a national program for prevention, early detection, and control of hypertension.